Accumulation of Amino Acids and Flavonoids in Young Tea Shoots Is Highly Correlated With Carbon and Nitrogen Metabolism in Roots and Mature Leaves - Liu, Jianwei; Liu, Meiya; Fang, Hanhan; Zhang, Qunfeng; Ruan, Jianyun (Frontiers in Plant Science, 2021)
The quality of tea product and the metabolism of quality-related compounds in young shoots are significantly affected by the nitrogen (N) supply. However, little is known of the metabolic changes that take place in tea roots and mature leaves under different supplies, which has a large effect on the accumulation of quality-related compounds in young shoots. In this study, young shoots, mature leaves, and roots under different N conditions were subjected to metabolite profiling using gas chromatography and ultraperformance liquid chromatography, coupled with quadrupole time-of-flight mass spectrometry. The contents of free amino acids (e.g., theanine and glutamate) involved in N metabolism were significantly greater under high N than under low N, while a high N supply reduced soluble sugars (e.g., glucose) in all three tissues. Organic acids (e.g., malatefumarate, ketoglutarate, and succinate) involved in tricarboxylic acid cycle remarkably increased as the nitrogen supply increased, which confirms that carbon (C) allocation was restricted by increasing the N supply, especially in mature leaves. RT-PCR results indicated that gene expression related to nitrogen assimilation significantly increased in roots with increasing nitrogen supply, which had a significant positive relationship with the level of free amino acids in young shoots. In addition, the expression of most genes involved in flavonoid synthesis was significantly upregulated under conditions of low nitrogen supply relative to high nitrogen supply in young shoot and roots. These data suggest that enhanced assimilation of N in tea roots and the coordinated regulation of carbon (sugars, organic acids, and flavonoids) and nitrogen (amino acids) in mature leaves can lead to a high accumulation of amino acids in young shoots. Furthermore, as the N supply increased, more C was partitioned into compounds containing N in mature leaves and roots, resulting in a decrease in flavonoids in young shoots. In conclusion, the accumulation of amino acids and flavonoids in young tea shoots is highly correlated with carbon and nitrogen metabolism in roots and mature leaves.